2021
DOI: 10.3390/cancers13030458
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Neoadjuvant Therapies in HR+/HER2−Breast Cancers: Challenges for Improving pCR

Abstract: A strong association of pCR (pathological complete response) with disease-free survival or overall survival is clinically desirable. The association of pCR with disease-free survival or overall survival in ER+/HER2−breast cancers following neoadjuvant systemic therapy (NAT) or neoadjuvant endocrine therapy (NET) is relatively low as compared to the other two subtypes of breast cancers, namely triple-negative and HER2+ amplified. On the bright side, a neoadjuvant model offers a potential opportunity to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Luminal B tumors have a more aggressive phenotype, a higher histological grade, and a worse prognosis than those of the luminal A subtype [ 8 , 9 ]. Patients that are overexpressing HER2 are frequently treated with Trastuzumab (an humanized monoclonal antibody against this receptor) or, in most cases upon recurrence, lapatinib (an small molecular inhibitor of HER2 tyrosine kinase activity) [ 10 ]. Despite the implementation of these selective therapies against luminal and HER2 positive breast cancers, approximately 20–30% of the patients that are treated with endocrine therapy and 70% of patients that are treated with Trastuzumab develop resistance, and progress to a more advanced disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Luminal B tumors have a more aggressive phenotype, a higher histological grade, and a worse prognosis than those of the luminal A subtype [ 8 , 9 ]. Patients that are overexpressing HER2 are frequently treated with Trastuzumab (an humanized monoclonal antibody against this receptor) or, in most cases upon recurrence, lapatinib (an small molecular inhibitor of HER2 tyrosine kinase activity) [ 10 ]. Despite the implementation of these selective therapies against luminal and HER2 positive breast cancers, approximately 20–30% of the patients that are treated with endocrine therapy and 70% of patients that are treated with Trastuzumab develop resistance, and progress to a more advanced disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical examination of Bcl2 as antiapoptotic protein was carried out in breast tissue which showed increased expression in DMBA group. BCL2 is responsible for suppression of the mitochondrial pathway activation to apoptosis, and its expression is increased in most breast cancer cases [ 26 ]. Treatment with 7b mainly reduced BCL2 activity, thus induces apoptosis, and limits cancer progression [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCL2 is responsible for suppression of the mitochondrial pathway activation to apoptosis, and its expression is increased in most breast cancer cases [ 26 ]. Treatment with 7b mainly reduced BCL2 activity, thus induces apoptosis, and limits cancer progression [ 26 , 27 , 28 ]. The reduction of cancer size may be explained by the downregulation of Bcl2 and up-regulation of BAX, which leads to a shift in the Bcl2/BAX ratio towards a pro-apoptotic signal in 7b -treated group.…”
Section: Discussionmentioning
confidence: 99%
“…The recent phase II trial CORALLEEN in patients with high-risk luminal B breast cancer demonstrated response rates similar to multiagent chemotherapy with ribociclib/letrozole but with less toxicity ( 21 ). However, the demonstrated clinical efficacy of ribociclib and the other CDK4/6 inhibitors in metastatic settings cannot yet be translated in higher pathological complete response in neoadjuvant settings, where the role of targeted agents is still debated ( 22 ).…”
Section: Discussionmentioning
confidence: 99%